Adolescents’ participation opportunities and student well-being in school - Ott, Martina B.; Meusburger, Katharina M.; Quenzel, Gudrun (Frontiers in Education, 2023)
At school, it is important that young people are in an environment in which they feel well and have a positive attitude. To increase the positive attitude toward school as an indicator of the well-being of students, it is essential to know which factors influence it. Recent studies have indicated that participation opportunities at school might have a positive impact on the well-being of students. However, participation encompasses a wide range of different actions, decision-making processes, and forms of communication. This article explores different aspects of student participationdemocratic school culture, active co-design, pseudo-participation, and the co-determination of students in the classroom and in teaching-and its relationships to student well-being. This article has an exploratory design and uses representative secondary data (n = 1,526) of students in the 8th to 10th grades in Vorarlberg (Austria) for a multilevel analysis to examine different aspects of student participation that promote or reduce student well-being. The results show that a democratic school culture has the strongest correlation with student well-being. Students' co-determination and active co-design in the classroom and in teaching are also positively related to student well-being. Pseudoparticipation has a weak negative effect on student well-being. The results suggest that in order to promote student well-being, it is important to increase the democratic culture of schools, to involve students in as many decisions as possible, and to let them have a real say in the class.